Designing for affect through affective matter - Kidd, Akari; Smitheram, Jan (Interstices: Journal of Architecture and Related Arts, 2014)
This paper examines how affect moves us and specifically, how we can design affective environments rather than use affect as a tool for interpretation, analysis or description. In architecture, affect, for the most part, continues a Spinozean-Deleuzian lineage of recognising affect as prior to, or autonomous from, emotion and a subject-centred account of the world. This paper considers affect as a potentially materialized and localizable condition capable of being designed for. The paper develops two positions relative to materiality: firstly, a review of theoretical discourse on affect in the context of new materialism; and secondly, an examination of the pedagogical potential of affective and atmospheric materialities via design strategies we have called de-materializing, diagramming, and re-materializing. In conclusion, we offer some observations regarding the potential to design for affect to move us.